2002
DOI: 10.1097/00007632-200202010-00015
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Tuberculosis of Posterior Elements of Spine

Abstract: In tuberculosis of the posterior element of the spine, MRI is extremely useful in evaluating the extent of involvement and response to therapy of isolated tuberculosis of posterior elements. Involvement of posterior elements due to tuberculosis is not so uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Although not specific to spinal TB, there is a decrease in signal intensity of the involved bone and soft tissues on T2-weighted images and the increase in intensity of a uniform thin rim enhancement is a pathogenomic finding suggesting either caseation necrosis or a cold abscess in tuberculosis [16]. In the evaluation of spinal TB with isolated involvement of the posterior elements, MRI is also useful in diagnosis and assessment of the treatment response [17]. …”
Section: Diagnosismentioning
confidence: 99%
“…Although not specific to spinal TB, there is a decrease in signal intensity of the involved bone and soft tissues on T2-weighted images and the increase in intensity of a uniform thin rim enhancement is a pathogenomic finding suggesting either caseation necrosis or a cold abscess in tuberculosis [16]. In the evaluation of spinal TB with isolated involvement of the posterior elements, MRI is also useful in diagnosis and assessment of the treatment response [17]. …”
Section: Diagnosismentioning
confidence: 99%
“…[456789] Lower thoracic and lumbar vertebrae are the most common sites of spinal TB followed by middle thoracic and cervical vertebrae. [7101112131415] The second cervical to seventh cervical region is reportedly involved in 3-5% of cases and atlantoaxial articulation is less than 1% cases. In TB, involvement of posterior elements due to TB is not so uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…The lamina was most commonly involved followed by pedicles, articular processes, spinous processes, and transverse processes. [4567111216]…”
Section: Introductionmentioning
confidence: 99%
“…Associated posterior element involvement had been reported between 8% and 68%. [1422232728] On MR imaging, 109 vertebrae were involved in the study population comprising fifty patients. The average number of vertebrae affected per patients was 2.18.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Various authors have reported incidence of endplate erosions between 25% to 100%. [4613152728] Out of the total 62 discs at initial presentation; 53 showed discitis, 5 were spared, and 4 were destroyed. The reported incidence of disc involvement varies from 33% to 100%.…”
Section: Discussionmentioning
confidence: 99%